2016
DOI: 10.1515/znc-2016-0057
|View full text |Cite
|
Sign up to set email alerts
|

LC/ESI-MS/MS profiling of Ulmus parvifolia extracts and evaluation of its anti-inflammatory, cytotoxic, and antioxidant activities

Abstract: In this study, a comparative liquid chromatography/mass spectroscopy (LC/ESI-MS/MS) profiling of different fractions of Ulmus parvifolia leaves and stems was performed. Identification of compounds was based on comparing the mass spectrometric information obtained including m/z values and individual compound fragmentation pattern to tandem mass spectral library search and literature data. Eleven compounds were tentatively identified in the different analyzed fractions. One of the major constituents of this plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Several Ulmus species reportedly possess anti-oxidative (Jung et al, 2010) and anti-platelet (Yang et al, 2013) properties. Ulmus parvifolia Jacq., commonly known as the Chinese Elm or Lacebark Elm, is native to Korea, Japan, and China, reportedly possesses anti-inflammatory (Mina et al, 2016), anti-allergic (Kim et al, 2016), anti-viral, and anticancer (Hamed et al, 2015) properties. While investigating newer and safer efficacious ethnomedicinal products, we recognized the medicinal properties of U. parvifolia bark.…”
Section: Introductionmentioning
confidence: 99%
“…Several Ulmus species reportedly possess anti-oxidative (Jung et al, 2010) and anti-platelet (Yang et al, 2013) properties. Ulmus parvifolia Jacq., commonly known as the Chinese Elm or Lacebark Elm, is native to Korea, Japan, and China, reportedly possesses anti-inflammatory (Mina et al, 2016), anti-allergic (Kim et al, 2016), anti-viral, and anticancer (Hamed et al, 2015) properties. While investigating newer and safer efficacious ethnomedicinal products, we recognized the medicinal properties of U. parvifolia bark.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive components, such as sesquiterpenoids, triterpenoids, flavonoids, coumarins, and lignans, are mainly present in this species [16]. It has been reported that UP has analgesic and anti-inflammatory effects [12,14]; however, its role in skin wound healing has not been reported. Therefore, in the present study, we demonstrated for the first time the skin wound healing effect of the root bark of UP in SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies on U. parvifolia Jacq. (UP), a species of elm native to China, Korea, and Japan, have shown that its leaves and stems have anti-inflammatory and antioxidant effects [12]. U. parvifolia bark, which contains phenolic compounds and steroidal glucosides, is used for the treatment of eczema and edema [13].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive components such as sesquiterpenoids, triterpenoids, flavonoids, coumarins, and lignans are mainly present in this species [15]. It has been reported that U. parvifolia have analgesic and anti-inflammatory effects [11,13]; however, its role in skin wound healing has not been reported. Therefore, in the present study, we have demonstrated for the first time the skin wound healing effect of the root bark of U. parvifolia in SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies on U. parvifolia Jacq. (UP), a species of elm native to China, Korea, and Japan, have shown that its leaves and stems have anti-inflammatory and antioxidant effects [11]. U. parvifolia bark, which contains phenolic compounds and steroidal glucosides, is used for the treatment of eczema and edema [12].…”
Section: Introductionmentioning
confidence: 99%